Change of speed in simulated cross-country ski racing: a kinematic analysis - Barberis,M.; Rouard, A.; Messenger, N. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of the study was to identify the kinematic changes of the diagonal stride technique (DST) associated to a decrease of speed during a simulated cross-country ski race. Eight male cross-country skiers skied a 15 km course composed of 6 laps of 2.5 km. Full DST cycles were recorded using a digital camera for each lap. The fastest and slowest laps for each skier were selected, from which the following variables were studied: (i) cycle length and cycle frequency, (ii) propulsion length and duration, (iii) swing length and duration and (iv) trunk and knee angles. The skiing speed was significantly decreased between the first and the second part of the simulated race. The speed change was associated only with modification of the spatial components of the DST cycle (cycle and phase lengths, trunk and knee angles). The cycle durations remained constant. It was concluded that the decrease of speed resulted from a deterioration of the technique reducing the application of propulsion forces.